The Plate Objective Scoring Tool (POST): Further Reflections and Extended Applications - Tariq O Abbas (18090619) (2021)
Hypospadias is a common birth defect of the male external genitalia. However, there are conflicting arguments about the optimal classification approach and ideal surgical technique. We have introduced the Plate Objective Scoring Tool (POST) to define critical glanular phenotypic landmarks of the urethral plate. We propose that POST can objectively, reproducibly, and accurately determine urethral plate quality, thus permitting robust comparison between the different surgical techniques commonly utilized in hypospadias repair. Furthermore, the POST scoring system represents a versatile tool that can objectively quantify key variables in hypospadiology that are currently not well defined. Further validation of POST should lead to better identification and management of postoperative complications. Other Information Published in: Research and Reports in Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/rru.s321188